MEASUREMENT AND COMPARISON OF LABOUR PRODUCTIVITY IN THE ASEAN - สว่างโลก วีระศักดิ์; สันติพลวุฒิ สุมาลี; ธรรมาอภิรมย์ เรวัตร (RMUTT Global Business and Economics Review, 2019)
The research aims to measure labour productivity of all countries of the Association of Southeast Asian Nations (ASEAN), using Cobb-Douglas production function and productivity index, and compare them with Cambodia, Lao PDR, Myanmar, and Vietnam (CLMV) and Brunei, Indonesia, Malaysia, the Philippines, Singapore, and Thailand (ASEAN6), based on income level, and the period of economic integration in the ASEAN from 1971–2016. The findings show that the average product of labour (APL), marginal product of labour (MPL), and the labour productivity index (LPI) in the ASEAN6 are likely to decrease, while continuously increasing in CLMV. When comparing labour productivity with national development based on income level, high-income economies are found to have the highest labour productivity in comparison to upper-middle-income and lower-middle-income economies. The comparison of labour productivity by economic integration demonstrates that the first period of economic integration from 1971–1991 produced a relatively low level of labour productivity in all countries. Later, from 1992–2016, there were more agreements and concrete economic integration, leading to an increase in labour productivity within the region.